Positive Allosteric Modulation of mGluR5 Accelerates Extinction Learning but Not Relearning Following Methamphetamine Self-Administration - Kufahl, Peter R.; Hood, Lauren E.; Nemirovsky, Natali E.; Barabas, Piroska; Halstengard, Casey; Villa, Angel; Moore, Elisabeth; Watterson, Lucas R.; Olive, M Foster (Frontiers in Pharmacology, 2012)
Recent studies have implicated glutamate neurotransmission as an important substrate for the extinction of conditioned behaviors, including responding for drug reinforcement. Positive allosteric modulation of the type-5 metabotropic glutamate receptor (mGluR5) in particular has emerged as a treatment strategy for the enhancement of extinction of drug-motivated behaviors. Here, we investigated the effects of the mGluR5 positive allosteric modulator CDPPB, a compound known for its cognitive enhancing effects in rodents, on extinction learning in rats with different histories of methamphetamine (METH) training. Rats were trained to self-administer METH under two conditions: 16 daily sessions of short access (90 min/day, ShA), or 8 daily sessions of short access followed by 8 sessions of long access (6 hr/day, LgA). Control rats self-administered sucrose pellets in daily 30 min sessions. Next, rats were administered vehicle or 30 mg/kg CDPPB prior to 7 consecutive daily extinction sessions, subjected to additional extinction sessions to re-establish a post-treatment baseline, and then tested for reinstatement of behavior in the presence of METH- or sucrose-paired cues. Rats were then subjected to a second series of extinction sessions, preceded by vehicle or 30 mg/kg CDPPB, and an additional test for cue-triggered reinstatement. CDPPB treatment resulted in a more rapid extinction of responding on the active lever, especially in the early sessions of the first extinction sequence. However, treatment effects were minimal during subsequent cue reinstatement tests and nonexistent during the second series of extinction sessions. Rats with histories of ShA, LgA and sucrose training expressed similar behavioral sensitivities to CDPPB, with LgA rats demonstrating a modestly higher treatment effect. Positive allosteric modulation of mGluR5 may therefore have some beneficial effects on efforts to facilitate extinction learning and reduce methamphetamine seeking.